Strong Convergence for Hybrid S-Iteration Scheme - Shin Min Kang; Arif Rafiq; Young Chel Kwun (Journal of Applied Mathematics)
We establish a strong convergence for the hybrid S-iterative scheme associated with nonexpansive and Lipschitz strongly pseudocontractive mappings in real Banach spaces.